Uma abordagem para manipulação de informações geográficas utilizando Scalable Vectors Graphics - Cabral, Igor Pinheiro de Sales (2006)
In this work, we propose a Geographical Information System that can be used as a tool for the treatment and study of problems related with environmental and city management issues. It is based on the Scalable Vector Graphics (SVG) standard for Web development of graphics. The project uses the concept of remate and real-time mar creation by database access through instructions executed by browsers on the Internet. As a way of proving the system effectiveness, we present two study cases;.the first on a region named Maracajaú Coral Reefs, located in Rio Grande do Norte coast, and the second in the Switzerland Northeast in which we intended to promote the substitution of MapServer by the system proposed here. We also show some results that demonstrate the larger geographical data capability achieved by the use of the standardized codes and open source tools, such as Extensible Markup Language (XML), Document Object Model (DOM), script languages ECMAScript/ JavaScript, Hypertext Preprocessor (PHP) and PostgreSQL and its extension, PostGIS